Notes on fungus gnats from the East Mediterranean with description of two new species (Diptera: Sciaroidea excl. Sciaridae). - Kurina, Olavi (Contributions to Entomology = Beiträge zur Entomologie, 2004)
Data on 24 fungus gnat species collected from the Greek mainland, Corfu Island, Greek islands adjacent to Asia Minor and Cyprus are presented. Two new species – Macrorrhyncha atticae sp. nov. and Megophthalmidia samosica sp. nov. – are described and detailed illustrations of genitalia for both species are given. The second known specimen is found for Ectrepesthoneura ledenikiensis Bechev. Macrocera levantina Chandler is recorded from Europe for the first time. Keywords Diptera, Keroplatidae, Mycetophilidae, Macrorrhyncha, Megophthalmidia, new species, Greece, Cyprus. Nomenclatural Acts atticae Kurina, 2004 (Macrorrhyncha), spec. n. samosica Kurina, 2004 (Megophthalmidia), spec. n.